Negative Politeness Strategies of Mbojo Speakers in a Family Environment: A Linguistics Study of Sociopragmatic - Sahrain, Muhammad (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2024)
This study aims at describing negative politeness principle strategies carried on Mbojo Speakers in a Family Environment by applying socio-pragmatics analysis, it’s a sub-dicipline of linguistics. Data were collected from speech events in Mbojo family environment and further analyzed descriptively. In the process of analyzing the data applies the theory of negative politeness strategies proposed by Brown and Levinson. The result shows that from seven strategies of negative politeness, in speech events of the Mbojo family Environment, there are four negative politeness strategies were found, including Strategy of Using Indirect Expressions, Strategy Use Hedge Honorin, Strategy Using impersonal form.